Developing a Pictorial Scale of Mindfulness for Kindergarten Children (Journal of the College of Basic Education, 2026)
The present study aims to construct a pictorial scale of mindfulness for kindergarten children, The two researchers prepared the mindfulness scale after reviewing the relevant theories and previous studies related to the subject of the study, The mindfulness scale consisted of 30 items distributed across five domains, with each domain comprising six items, The researchers prepared the scale instructions and the pictorial illustrations for each item in accordance with the scientific guidelines for scale construction, The scale was scored using three alternatives (3–2–1). The researchers verified the psychometric properties of the scale by establishing validity through two methods: face validity and construct validity, The reliability of the scale was also determined using the test–retest method and Cronbach’s alpha coefficient.